1994
DOI: 10.1093/nar/22.24.5371
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of DNA binding ligands with PNA-DNA hybrids

Abstract: The interactions of two representative mixed-sequence (one with an AT-stretch) PNA -DNA duplexes (10 or 15 base-pairs) and a PNA2/DNA triplex with the DNA binding reagents distamycin A, 4',6-diamidino-2-phenylindole (DAPI), ethidium bromide, 8-methoxypsoralen and the A and A enantiomers of Ru(phen)2-dppz2+ have been investigated using optical spectroscopic methods. The behaviour of these reagents versus two PNA -PNA duplexes has also been investigated. With triple helical poly(dA)/(H-T10-Lys-NH2)2 no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 18 publications
3
71
0
1
Order By: Relevance
“…This is noteworthy in light of previous investigations in which typical intercalators, such as ethidium bromide, 8-methoxypsoralen, and RuA C H T U N G T R E N N U N G (phen) 2 dppz 2 + , did not exhibit increases in fluorescence upon exposure to PNA·DNA duplexes. [41] However, analysis of the fluorescence titration data ( Figure 6C, D) revealed that TO-PRO1 binds PNA·DNA duplex 3·2 with lower affinity (K app = 7.3 AE 0.4 mm per base pair) than DNA·DNA duplex 1·2 (K app = 134 AE 20 mm per base pair) ( Table 1). Most remarkable were the results obtained with FIT-PNA complexes 4.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is noteworthy in light of previous investigations in which typical intercalators, such as ethidium bromide, 8-methoxypsoralen, and RuA C H T U N G T R E N N U N G (phen) 2 dppz 2 + , did not exhibit increases in fluorescence upon exposure to PNA·DNA duplexes. [41] However, analysis of the fluorescence titration data ( Figure 6C, D) revealed that TO-PRO1 binds PNA·DNA duplex 3·2 with lower affinity (K app = 7.3 AE 0.4 mm per base pair) than DNA·DNA duplex 1·2 (K app = 134 AE 20 mm per base pair) ( Table 1). Most remarkable were the results obtained with FIT-PNA complexes 4.…”
Section: Resultsmentioning
confidence: 98%
“…Previous investigations by NordØn showed that traditional intercalators, such as ethidium, methoxypsoralen, and ruthenium dipyridinophenazine complexes, failed to bind to PNA·DNA duplexes, whereas minor groove binders, such as DAPI (4',6-diamidino-2-phenylindole) and distamycin, showed modest binding affinities. [41] Armitage demonstrated that the minor groove of PNA·DNA duplexes provides a high-affinity template for the aggregation of the symmetrical cyanine dye DiSC 2 . [42,43] We have not attempted to resolve the stoichiometry of TO-PRO1·PNA·DNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In the hybridized state, the dye can either fold back, binding to the PNA-DNA duplex (or PNA 2 -DNA triplex), or it can bind to the protruding single-stranded DNA. We think the latter dominates since intercalating dyes in general have very low affinity for PNA-DNA duplexes (and PNA 2 -DNA triplexes) (19), while TO has substantial affinity for single-stranded DNA (16). Still the spectroscopic properties of the probes in the hybridized state varied slightly, although the protruding sequences were the same in all constructs (Table 2).…”
Section: Fluorescence Enhancement Of Light-up Probes Upon Hybridizationmentioning
confidence: 98%
“…It appears that the only additional requirement for recognition by the enzyme is phosphate groups on the dimer-containing strand (3,4). For these reasons, we suspected that photolyase might retain its ability to recognize and repair thymine dimers contained on the DNA strand of a DNA͞PNA hybrid duplex (5)(6)(7)(8). We carried out a series of experiments to assess this possibility.…”
mentioning
confidence: 99%